f-8-3f=37f+4

Simple and best practice solution for f-8-3f=37f+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f-8-3f=37f+4 equation:


Simplifying
f + -8 + -3f = 37f + 4

Reorder the terms:
-8 + f + -3f = 37f + 4

Combine like terms: f + -3f = -2f
-8 + -2f = 37f + 4

Reorder the terms:
-8 + -2f = 4 + 37f

Solving
-8 + -2f = 4 + 37f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-37f' to each side of the equation.
-8 + -2f + -37f = 4 + 37f + -37f

Combine like terms: -2f + -37f = -39f
-8 + -39f = 4 + 37f + -37f

Combine like terms: 37f + -37f = 0
-8 + -39f = 4 + 0
-8 + -39f = 4

Add '8' to each side of the equation.
-8 + 8 + -39f = 4 + 8

Combine like terms: -8 + 8 = 0
0 + -39f = 4 + 8
-39f = 4 + 8

Combine like terms: 4 + 8 = 12
-39f = 12

Divide each side by '-39'.
f = -0.3076923077

Simplifying
f = -0.3076923077

See similar equations:

| 3y-3=5y-5 | | f-8-3f=3-7f | | 84-3=6y+17 | | 11x=7x-20 | | 23-x=22 | | (2x+1/3)^2=0 | | 55=(3x-1)(5) | | 2(2k-5)-k=4-(3k+7) | | 49-x=14 | | -16-8= | | 26X+12=5(5X+7) | | 10+2-x/3=7 | | 32n+12-20=12n+16+1 | | 9d/12-d/12 | | v*7=8 | | 70=(x+4)(7) | | m*4=-13 | | (-8x-4y/2x)+(6x-11y/2x) | | 6x+10=-6+58 | | 2(y+5)=3(y-15)+20 | | 4=(.300+x)(.200+x) | | 1/4(x-12) | | 15x+10y=90 | | -1/2(8+6) | | 15x+10x=90 | | 7(8-3)= | | k=k*11 | | -2z-4(10-4z)=-2 | | 36x+11=5x^2 | | -4(x-4)-2x=8-6(x+3) | | 3a-a+1=5 | | 5=2(3-8q)-2q |

Equations solver categories